Analisis Pencatatan Dan Pelaporan Keuangan Pada Dinas Pemadam Kebakaran Dan Penyelamatan Kota Padangsidimpuan - Siagian, Adelini; Saparuddin, Saparuddin (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
The realization of good government in each region requires transparency and openness from the public sector so that the public can control and improve the performance of local governments. This paradigm gives the government the widest possible autonomy but must be balanced with proper regional financial management. APBD stands for â€œAnggaran Pendapatan dan Belanja Daerahâ€ in Indonesian, which translates to â€œRegional Government Budgetâ€ in English. APBD is a strategic agenda in improving peopleâ€™s welfare. Not all regions succeed in functioning the APBD properly. The aim of the study was to find out whether the Padangsidimpuan City Fire and Rescue Service had properly recorded or not (according to Permendagri No. 13 of 2006 and PP No. 24 of 2005 concerning Regional Financial Management) as a reference. The research methodology in the authorâ€™s research is a qualitative research design that aims to understand the data obtained in the form of notes and financial reports. The types of data used are primary data and secondary data and the data obtained, namely by field research data collection techniques and library research.